Gordonibacter faecis sp. nov., producing urolithin C from ellagic acid, isolated from feces of healthy Korean subjects - Kim, Han Sol; Kim, Ji-Sun; Suh, Min Kuk; Eom, Mi Kyung; Do, Hyo Eun; Lee, Ju Huck; Park, Seung-Hwan; Kang, Se Won; Lee, Dong Ho; Yoon, Hyuk; Lee, Je Hee; Lee, Jung-Sook (Archives of microbiology, 2024)
A Gram-stain-positive, anaerobic, motile, and short rod-shaped bacterium, designated KGMB12511 T , was isolated from the feces of healthy Koreansubjects. Phylogenetic analysis based on the 16S rRNA gene sequence showed that strain KGMB12511 T was closely related to Gordonibacter pamelaeae 7-10-1-b T (95.2%). The draft genome of KGMB12511 T comprised 33 contigs and 2,744 protein-coding genes. The DNA G + C content was 59.9% based on whole-genome sequences. The major cellular fatty acids (>10%) of strain KGMB12511 T were C 18:1 cis 9, C 18:1 cis 9 DMA (dimethylacetal), and C 16:0 DMA. The predominant polar lipids included a diphosphatydilglycerol, four glycolipids, and an unidentified phospholipid. The major respiratory quinones were menaquinone 6 (MK-6) and monomethylmenaquinone 6 (MMK-6). Furthermore, HPLC analysis demonstrated the ability of strain KGMB12511 T to convert ellagic acid into urolithin. Based on a comprehensive analysis of phenotypic, chemotaxonomic, and phylogenetic data, strain KGMB12511 T represents a novel species in the genus Gordonibacter . The type strain is KGMB12511 T (= KCTC 25343 T = NBRC 116190 T ).